Numerical investigation on the gas entrainment rate on ventilated supercavity body. (December 2016) - Yang, WuGang; Yang, ZhenCai; Wen, KaiGe; Yang, ZhaoHui; Zhang, YuWen
The supercavitation technique provides a means of significantly increasing the velocity of an underwater vehicle. This technique involves essentially the creation of stable supercavity shape. The method of artificial ventilation is most effective for generating and dominating the supercavity. This paper focuses on the numerical simulation of flow field around three-dimensional body. The method is based on the multiphase computational fluid dynamics model combined with the turbulence model and the full cavity model. The fundamental similarity parameters of ventilated supercavity flows that include cavitation number, Froude number Fr, entrainment rate C Q, and drag coefficient Cx are all investigated numerically in the case of steady flow and gravity field. We discuss the following simulations results in three parts: (1) the variations of the cavitation number and the supercavity's relative diameter with entrainment rate; (2) the drag coefficient versus the cavitation number; and (3) deformation of supercavity axis caused by gravitational effect for three different fixed three Froude numbers. In the full paper, we give the comparison results of the drag reduction ratio among numerical simulation and experiment conducted in hydrodynamic tunnel and towing tank, respectively. We summarize our discussion of gravitational effect on the axis deformation of supercavity as follows: in the case of smaller Froude number, the inclination of the cavity axis increases monotonously with increasing horizontal length and reaches its maximal value at the end of supercavity; this deformation can be almost completely negligible when the Froude number Fr is larger than 7.0. The comparisons with the experimental data in the hydrodynamic tunnel and the towing tank indicate that the present method is effective for predicting the flows around ventilated supercavity; that the numerical results is in good agreement with the experimental ones and that the maximal value of the drag reduction ratio can be expected to reach the value of 90% compared with that of the condition of non-cavitation.